Optimization of conditions for improved solar energy harvesting application by hydrothermally grown TiO2 nanorods - Mansoor, Muhammad Adil; Yusof, Farazila; Huang, Nay Ming (Iranian Chemical Society, 2019)
In this study, using the optimum annealing temperature and time for hydrothermally grown TiO 2 nanorods, photooxidation of water at different pH values of the electrolyte solution is investigated. The composition, crystallinity and topographic studies of films, sintered at different temperatures of 200–500 °C for 2 h and annealed for 1–4 h at 400 °C, were evaluated by X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy and field emission scanning electron microscopy. The sintering at high temperature and for longer time demonstrates an increase in crystallinity, but at the same time agglomeration of nanorods for prolonged heating and at high temperature leads to cracking at the surface of the films. Further, UV–Vis spectroscopic studies revealed prolonged heating and high-temperature sintering resulted in a red shift in light absorption edge of the films. The chronoamperometric measurement results under regular interrupted chopping revealed that the sample annealed at 400 °C for 2 h gives the best photoelectrochemical response with photocurrent density of 522 µA cm − 2 using 0.5M NaOH. The chronoamperometric response under different pH values of 13.7, 7.2 and 2.5 proved that TiO 2 gives the best response under a basic pH of 13.7 and the least under acidic media. The electrochemical impedance studies provided an insight into the charge transfer mechanism under dark and illumination with R ct value of 1188.8 Ω under dark and 164.5 Ω under light conditions for the film annealed at 400 °C for 2 h. [Figure not available: see fulltext.]. © 2019, Iranian Chemical Society.